1989
DOI: 10.1056/nejm198905183202005
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial Hyperresponsiveness to Methacholine in Patients with Impaired Left Ventricular Function

Abstract: To elucidate the pathogenesis of bronchospasm in congestive heart failure, we studied 23 patients with chronic impairment of left ventricular function due to coronary artery disease or dilated cardiomyopathy. In 21 of them we found marked bronchial hyperresponsiveness to methacholine. The mean dose (+/- SD) of methacholine that elicited a 20 percent decrease in the forced expiratory volume in one second (FEV1) was 421 +/- 298 micrograms, nearly the same as in patients with symptomatic asthma. In contrast, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
118
3
2

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(129 citation statements)
references
References 23 publications
6
118
3
2
Order By: Relevance
“…Only a very small minority will develop the disease de novo after this age. In older individuals, increased bronchial responsiveness is an even less specific marker for asthma, as it is also found in chronic obstructive pulmonary disease (COPD), left ventricular dysfunction, and even in healthy elderly individuals (7). In a longitudinal survey study of respiratory disease, Burrows et al (8) showed that among asthmatic patients newly diagnosed over the age of 60, two-thirds had respiratory symptoms, and one-third had obstructive defects in lung function for a mean period of 8.5 years prior to the diagnosis.…”
Section: Diagnosis Of Asthmamentioning
confidence: 99%
“…Only a very small minority will develop the disease de novo after this age. In older individuals, increased bronchial responsiveness is an even less specific marker for asthma, as it is also found in chronic obstructive pulmonary disease (COPD), left ventricular dysfunction, and even in healthy elderly individuals (7). In a longitudinal survey study of respiratory disease, Burrows et al (8) showed that among asthmatic patients newly diagnosed over the age of 60, two-thirds had respiratory symptoms, and one-third had obstructive defects in lung function for a mean period of 8.5 years prior to the diagnosis.…”
Section: Diagnosis Of Asthmamentioning
confidence: 99%
“…Airway edema, bronchial hyper-responsiveness, and peribronchial cuffing are commonly associated with aortic stenosis and volume overload, 12,13 and will often manifest as wheezing on exam. Indeed, up to one-third of patients older than age 65 with congestive heart failure present with cardiac asthma.…”
mentioning
confidence: 99%
“…Understanding the relationships between the pulmonary vasculature and bronchoalveolar networks has major importance in pathophysiological conditions encountered in various cardiopulmonary diseases, such as coronary ischaemia leading to left heart failure [3][4][5], congenital heart malfunctions [6,7] or valvular disfunction [5,8].…”
Section: Importance Of Cardiopulmonary Interactionsmentioning
confidence: 99%
“…Some authors demonstrated the induction of bronchial hyperresponsiveness (BHR) to lung provocations [3][4][5]8] whereas others found no evidence of BHR in patients with chronic congestive heart failure [24,25]. In addition to this controversy, the underlying pathophysiological mechanisms leading to airway narrowing and occasionally BHR after pulmonary lung congestion have not been completely clarified.…”
Section: Left Heart Failure and Lung Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation